Perineural infiltration of the inferior alveolar nerve in mandibular ameloblastomas - Engelbrecht, Hanlie (My University, 2013)
Introduction: Ameloblastomas are locally aggressive with a high recurrence rate, warranting continuity jaw resection. The preservation of the inferior alveolar nerve during ablative surgery in the treatment of ameloblastoma is contentious. Studies have suggested salvaging the nerve by pulling it out of the tumour prior to resection. There are presently no studies that have explored the surgical merit of nerve preservation in the treatment of ameloblastomas. Aim: To determine the histological association of mandibular solid and multicystic ameloblastoma to the inferior alveolar nerve, in situ and in separately removed segments of the nerve in order to determine the feasibility of preserving the nerve during ablative surgery for mandibular ameloblastomas. Materials and Methods: 13 resected hemimandibulectomy specimens were histologically examined with respect to the course and association of the inferior alveolar canal/nerve and the ameloblastoma. In group 1 (8 patients) this association was examined with the nerve within the mandibular segment following resection whilst in group 2 (5 patients) the nerve was explanted from the resected tumour and examined separately. In group 1 the closest histologic distance between tumour cells and the inferior alveolar canal was measured. Results: Perineural and intraneural ameloblastoma involvement of the inferior alveolar nerve was confirmed in 62.5% and 40% of cases in groups 1 and 2 respectively. Tumour cells were noted abutting directly onto the nerve in Group 1. Tumour cells were removed together with the pulled out nerve in Group 2. There was no correlation between the histological variants of ameloblastoma and the presence of tumour either in situ or within the pulled-out nerve bundle. Conclusion: Both peri- and intraneural involvement of the inferior alveolar nerve was histologically confirmed in solid and multicystic hemimandibular specimens both in situ within the tumour as well as in separately removed segments of the nerve. Preservation of the inferior alveolar nerve during ablative surgery for mandibular ameloblastomas cannot be advocated.
Keywords: Mouth Neoplasms